Blockchain technology to improve supply chain management - a systematic literature review - Beserra, Piera Beatriz (2021)
This study followed the systematic literature review approach to analyse how blockchain technology can improve supply chain management and to promote a future research agenda. The search was carried out at Web of Science Core Collection between September 2019 and February 2020 by using the keywords “blockchain” AND “supply chain” OR “blockchain” AND “logistics” in the title. In this review 127 studies were identified for screening and a final sample of 67 studies met the inclusion criteria and were analysed to answer the research questions. After examining the selected studies, our findings uncover a range of approaches showing how blockchain can enhance the supply chain management and point out which sectors are most likely to benefit from its implementation. This study contributes to the existing literature by systematising the most relevant information on blockchain implementation in supply chains. In addition, the findings of this study also provide managers and researchers with insights about the likely consequences of blockchain adoption in various sectors. Although there are already some literature reviews on blockchain technology in the supply chain management, this is one of the first studies that brings together the main issues focused on the consequences of blockchain adoption in the supply chain management.